2004
DOI: 10.1007/s00421-004-1107-4
|View full text |Cite
|
Sign up to set email alerts
|

In vivo determination of triceps surae muscle?tendon complex viscoelastic properties

Abstract: Viscoelastic properties of muscles and tendons have an important influence on human motion performance. Proper determination of these properties is essential in the analysis and modelling of human motion dynamics. The purpose of our study was to develop a method for in vivo determination of the viscoelastic properties of the entire triceps surae muscle-tendon complex (MTC) including the gastrocnemius. Ten trained male subjects participated in this study. The measurement procedure consisted of two parts: soleus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 20 publications
2
34
2
Order By: Relevance
“…Although biomechanical studies have shown that tendon stiffness increased in tendons such as tibialis posterior or Achilles after long exercise, in the present study no differentiation was found between tendon elasticity features between professional athletes' and healthy volunteer tendons [21]. In addition, the impact of physical activity on tendon elasticity biomechanical studies also point out that viscoelastic properties of the normal Achilles tendon varies with age and sex [22,23]. As our study, Drakonaki et al did not find any difference with age or sex [12].…”
Section: Discussioncontrasting
confidence: 84%
“…Although biomechanical studies have shown that tendon stiffness increased in tendons such as tibialis posterior or Achilles after long exercise, in the present study no differentiation was found between tendon elasticity features between professional athletes' and healthy volunteer tendons [21]. In addition, the impact of physical activity on tendon elasticity biomechanical studies also point out that viscoelastic properties of the normal Achilles tendon varies with age and sex [22,23]. As our study, Drakonaki et al did not find any difference with age or sex [12].…”
Section: Discussioncontrasting
confidence: 84%
“…cSWE uses localized measurements of the tendon to determine both the shear and viscous components. The viscosity of tendon acts as the dampening mechanism [24], which means a larger viscosity leads to an increased resistance to lengthening (i.e., increased stiffness) with an increased loading rate. This effect may act as a defensive mechanism by reducing the amount of tendon stretch; on the other hand, increased viscosity enables the tendon to transmit larger forces which may increase the risk of tendon injuries.…”
Section: Discussionmentioning
confidence: 99%
“…However, while height and weight are quite similar in what respect to this study and the study by Babic and Lenarcic, 13 are significantly higher than those corresponding to the population of the study by Fukashiro et al 12 For each load level, experimental tests were replicated four times to check the level of repeatability of measurements. For this purpose, tests were performed sequentially without altering the general configuration of the testing apparatus and taking a proper time interval lasting several seconds between each replication.…”
Section: Resultsmentioning
confidence: 80%
“…Once the values of the five unknown parameters were determined by minimizing the error functional O (equation (29)), the values of stiffness K and damping C of the equivalent vibrating system were calculated with equations (13) and (14) for the first load case. The reaction force f developed in the TS was calculated with equation (16).…”
Section: Processing Of Experimental Data and Extraction Of Ts Visco-ementioning
confidence: 99%
See 1 more Smart Citation